Menthol–thymol NADES as a fungicidal and chemosensitizing agent against multidrug-resistant Candida albicans: ROS induction, efflux pump inhibition, and synergy with fluconazole - Negro, Melisa Fabiana; Bustos, Pamela Soledad; Bellezze, Lautaro; Ortega, María Gabriela; Echeverría, Javier; Silva, María Fernanda; Peralta, Mariana Andrea (Frontiers in Pharmacology, 2025)
BackgroundThe increasing prevalence of azole-resistant Candida albicans (RCa) poses a critical therapeutic challenge, necessitating innovative antifungal approaches. Natural deep eutectic solvents (NADES), derived from natural metabolites such as terpenes, provide a promising and sustainable platform for delivering bioactive compounds with intrinsic pharmacological properties.PurposeThis study evaluated a eutectic system composed of menthol and thymol (MT NADES, 1:1 M ratio) for its antifungal efficacy against a multidrug-resistant clinical C. albicans strain.Materials and methodsThe antifungal activity of MT NADES was evaluated against a clinical C. albicans strain resistant to azole antifungals (RCa). The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) were determined using the broth microdilution method, following the CLSI M27-A4 guidelines. Synergistic effects with fluconazole were assessed through checkerboard microdilution and disc diffusion assays, with the fractional inhibitory concentration index (FICI) calculated to quantify interactions. Intracellular reactive oxygen species (ROS) levels were quantified using DCFH-DA staining and fluorescence spectrophotometry. Efflux pump inhibition was investigated via Nile red accumulation assay, analyzed by flow cytometry, using tacrolimus (100 µM) as a positive control. All experiments were performed in triplicate.Results and discussionMT NADES demonstrated potent fungicidal activity against resistant C. albicans with an MIC of 180 μg/mL and MFC of 360 μg/mL (MFC/MIC = 2), outperforming its components (menthol: 1000 μg/mL; thymol: 200 μg/mL). Synergistic interaction with fluconazole (MIC: 32 μg/mL) was confirmed by checkerboard and disc diffusion assays (FICI: 0.2839). Mechanistic studies revealed increased intracellular ROS, supporting oxidative stress as a key antifungal mechanism. Additionally, MT NADES at half its MIC enhanced Nile red retention 10-fold over the efflux pump inhibitor tacrolimus (100 µM), indicating strong inhibition of multidrug resistance (MDR)-related transporters. These findings highlight MT NADES as a promising chemosensitizing agent with superior efficacy over its individual components.ConclusionThese findings underscore the therapeutic potential of menthol–thymol NADES as a multifunctional, plant-derived antifungal strategy capable of overcoming multidrug resistance mechanisms and potentiating azole efficacy in C. albicans.